The game model of investing in the academic cloud - Bakhytzhan Akhmetov; Valery Lakhno; Nurzhamal Oshanova; Volodimir Malyukov; Zhuldyz Alimseitova; Aliza Turgnbayeva; Inna Malyukova; Miroslav Lakhno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2024)
The article analyzes approaches to the use of cloud technologies in the process of teaching students at large universities. The model of the academic cloud of a modern university is considered. Examples of software and functional platforms that meet the needs of students in electronic learning resources are given. The deployment models of the cloud-oriented educational environment that includes private cloud infrastructure as a service (IaaS) and platform as a university service are analyzed. The cost of deploying an academic cloud based on the educational institution’s infrastructure and renting infrastructure from a vendor is compared. A multifactorial model for evaluating investment options in the university cloud in the context of fuzzy information is proposed. In contrast to the known approaches to solving such a problem, our model assumes that the dynamics of the financial states of the players are set through a system of discrete equations. These equations describe the dynamics of multidimensional variables. The latter made it possible to consider the general problem of investing in the academic cloud within the framework of a game scheme for tasks in a fuzzy formulation, with the financial resources available to the educational institution. Preference sets and optimal financial allocation strategies for building an academic cloud are found.